Stone Circles at Raedykes, near Stonehaven, Kincardineshire (Proceedings of the Society of Antiquaries of Scotland, 1923)
Raedykes is well known for its Roman Camp, however, there are also four circles or ring-cairns on the site. The four circles are situated within a short distance of each other, so that a line joining their centres would form a slight curve little more than a hundred yards in length. They are nearly equal in size, and each consists of a ring-shaped cairn with a hollow centre, the interior depression and the exterior circumference being bounded by a setting of earthfast stones, set upright to support the smaller loose stones of which the cairns are composed. Only two of these ring-cairns, the most northerly and the most southerly, are surrounded by standing stones, and each is furnished with a circle of upright stones placed at a distance of a few feet beyond the outer circumference of the cairn. The recumbent\r stone, so important a feature in the Aberdeenshire type of circle, is entirely absent.